Pengaruh Budaya Organisasi Dan Kepuasan Kerja Dengan Pengembagan Karier Sebagai Variabel Moderasi Terhadap Kinerja Penyidik - Rochim, Bella; Novandalina, Arini; Marnoto, Marnoto; Sunarto, St; Prabowo, Catur (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze the influence of job satisfaction and organizational culture on investigator performance moderated by career development. The population is 173 investigators at the Central Java Regional Police Criminal Investigation Directorate. The sample size is 64. The sampling technique is non-probability sampling in the form of accidental sampling with a questionnaire data collection method. The quantitative analysis method uses Moderated Regression Analysis. The results show that organizational culture has no significant effect on Investigator Performance, job satisfaction has a significant effect on Investigator Performance, career development moderates positively and significantly the effect of organizational culture on investigator performance is not proven and can be interpreted that career development will not strengthen the influence of organizational culture on Investigator Performance and career development moderates positively and significantly the effect of job satisfaction on investigator performance is proven and can be interpreted that good career development will strengthen the effect of job satisfaction on Performance. The coefficient of determination is 0.860, meaning that organizational culture, job satisfaction and career development have a role of 86.0% together explaining the investigator performance variable. Suggestions for improving organizational culture through improving existing conditions, it is hoped that the organization can pay more attention to aspects of compensation and promotion, as well as the need to implement a leadership style through improving matters related to member efforts in achieving their goals and the need to increase the satisfaction of investigator members by paying attention to aspects of compensation and promotion